Factor Influencing Indonesian Consumer Intention to Adopt Electric Vehicle - I Gusti Agung Dharmayanaa; Ina Agustini Murwani; Henky Wibowo; Laksito Ardhi, Enggar (Jurnal Manajemen, 2026)
Electric vehicles (EVs) have become a new trend in Indonesia, despite low penetration rates. While EVs are promoted as a solution to environmental issues, the primary motivations for consumer purchase remain unclear. This chapter analyses the factors influencing Indonesian consumers' purchase intentions, specifically examining environmental attitudes, economic benefits, charging risks, technological risks, and policy incentives. Data were collected from a survey of 200 respondents and analysed using SEM-PLS. This chapter concludes that environmental factors are not significantly related to EV adoption intention; the dominant drivers are economic factors and risk perception. Furthermore, policy incentives were found not to moderate the relationship between these variables and adoption intention. The implications from this chapter include the need for stronger policies, enhanced charging infrastructure, improved after-sales services, and public education campaigns to increase EV adoption in Indonesia.